From Latin QUO(D) VELLES to Romagnol Cvël: A Case of Degrammaticalisation from a Free‐choice Indefinite to the Noun 'Thing'. - D'Antuono, Nicola (Transactions of the Philological Society, 2024)
Degrammaticalisation is an oft‐dismissed category of language change. In this paper evidence is provided for its existence, its triggers, and its conditions. This case study details the development of an understudied Old Italo‐Romance indefinite, covelle, a polarity‐sensitive item roughly translating as 'anything' which originated from a Latin free relative with Free‐Choice interpretation. It is shown that in Old Italo‐Romance the original Free Choice use was expanded to further nonveridical contexts. Subsequently, a curious development of covelle in Old Romagnol, a 16th‐century Gallo‐Italic variety, is examined whereby polar neutralisation (loss of sensitivity to polarity) of the indefinite was taking place. Contextually, a process of degrammaticalisation had begun through which the indefinite pronoun developed into the classifier 'thing'. In Modern and Contemporary Romagnol cvël is almost exclusively employed as a noun/classifier. It is argued that two parallel processes have initiated a cycle that led cvël to complete degrammaticalisation: (i) the grammaticalization of the old noun for 'thing', co(n)sa, into a wh‐word, calling for lexical replacement, and (ii) competition from the Negative Concord Item gnit. The development of covelle in Romagnol represents a well‐documented case of degrammaticalisation, whose causes and conditions can be thoroughly described and motivated within an interaction with cyclical change.